Effect of a Knowledge Translation Intervention on Physician Screening, Brief Intervention, and Referral to Treatment Behaviour in a Socioeconomically Disadvantaged Setting. Issue 1 (April 2015) - Dong, Kathryn; Vandenberghe, Christine; Kirkland, Scott; Cummings, Greta G.; McKim, Robert; Taylor, Marliss; Wild, Cameron T.
ABSTRACT: Objectives: : Screening, Brief Intervention and Referral to Treatment (SBIRT) is an effective but under‐utilized approach for managing alcohol and drug misuse in primary care and emergency settings. Implementing SBIRT with low socioeconomic position patients also requires attention to patient engagement. This study evaluated the impact of a knowledge translation intervention on physician SBIRT behaviour. Methods: : A nonrandomized, two‐group, pre‐post, quasiexperimental intervention design was used. Primary care and emergency physicians working with disadvantaged populations in a Canadian city were geographically allocated to control or intervention groups. Intervention physicians were offered a suite of activities including didactic sessions, electronic modules, point‐of‐care resources, and access to local champions. The primary outcome was physicians' self‐reported SBIRT practices. Chi‐square and ANOVA analyses compared intervention and control groups and assessed for participation effects. Subsequent regression analyses adjusted for confounding baseline characteristics. Results: : 131 physicians (78 intervention and 53 control) participated; 64 (49%) completed all follow up measures. Resources were well received, with uptake ranging from 25% (e‐modules) to 63% (point of care resources). After adjusting for demographics, baseline comfort level, and baseline SBIRT behaviour, the intervention was associated with an increase in SBIRT behaviour at 12 months. This effect was mediated by an increase in physician comfort working with the target population. Conclusions: : A SBIRT knowledge translation intervention for physicians working with low‐socioeconomically positioned patients was associated with an increase in comfort level, which in turn mediated an increase in physician‐reported SBIRT behaviour. Abstract : Objectifs: : Dépistage de l'abus d'alcool, intervention rapide et orientation (DIRO) est une approche efficace mais peu utilisée en contexte de soins de santé primaires et d'urgence pour la gestion de l'abus d'alcool et de drogues. Le processus d'implantation de DIRO auprès de patients à statut socioéconomique faible doit également tenir compte de l'engagement des patients. Cette étude a évalué, parmi des médecins, l'impact d'une intervention de transfert de connaissances sur les comportements en lien avec l'approche DIRO. Méthodologie: : L'intervention a respecté un devis quasi‐expérimental, pré‐post, de deux groupes répartis de façon non aléatoire. Des médecins qui travaillent en milieu de soins primaires et à l'urgence auprès de populations défavorisées d'une ville canadienne ont été géographiquement répartis dans un groupe contrôle ou expérimental. Les médecins du groupe expérimental se sont vus offrir des activités telles que des séances didactiques, des modules électroniques, des ressources au point de service et un accès aux champions locaux. Le principal résultat d'intérêt était les pratiques DIRO auto‐rapportées. Des analyses de la variance (ANOVA) et khi carré ont été réalisées pour comparer le groupe expérimental avec le groupe contrôle et évaluer les effets de la participation. Les analyses de régression subséquentes ont permis l'ajustement relatif aux facteurs confusionnels mesurés au début. Résultats: : 131 médecins (78 dans le groupe expérimental et 53 dans le groupe contrôle) ont participé; 64 (49% ont complété toutes les mesures au temps de suivi). Les ressources offertes ont été bien accueillies; le taux de participation aux modules électroniques était de 25% et celui pour les ressources au point de service de 63%. Après l'ajustement pour les données démographiques, le niveau de confort initial et les comportements DIRO initiaux, l'intervention est associée à une augmentation des comportements DIRO après 12 mois. Cet effet est facilité par un plus grand confort de la part des médecins à travailler avec des populations défavorisées. Conclusion: : Une intervention de transfert de connaissances sur l'approche DIRO auprès des médecins travaillant avec des patients à statut socioéconomique faible est associée à un plus grand confort des médecins qui, à son tour, favorise la pratique de l'approche DIRO tel qu'auto‐rapportée par les médecins.